1997
DOI: 10.1007/s004649900563
|View full text |Cite
|
Sign up to set email alerts
|

The dramatic reality of biliary tract injury during laparoscopic cholecystectomy

Abstract: Biliary tract injury is associated with significant mortality and complications in the practice of Belgian community surgeons. Intraoperative detection of ductal injury by the routine use and a correct interpretation of intraoperative cholangiography improved outcome. The impact of the primary biliary repair on long-term outcome is an argument to refer these patients to specialized multidisciplinary experts. The results highlight the importance of surgical experience, proper selection of patients for laparosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
5
15

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(147 citation statements)
references
References 34 publications
6
121
5
15
Order By: Relevance
“…Conversion rate was significant (estimated range 10-20%) 3. The rate of bile duct injury (BDI) was also significant (estimated above 0.5%), in reference to a previous national survey [9] There were 86 participating surgeons, 53 (62%) of whom accepted to include their consecutive AC patients into the study. A total of 35 hospitals were involved, including 7 academic and 28 peripheral hospitals.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Conversion rate was significant (estimated range 10-20%) 3. The rate of bile duct injury (BDI) was also significant (estimated above 0.5%), in reference to a previous national survey [9] There were 86 participating surgeons, 53 (62%) of whom accepted to include their consecutive AC patients into the study. A total of 35 hospitals were involved, including 7 academic and 28 peripheral hospitals.…”
Section: Methodsmentioning
confidence: 87%
“…In two other national multicenter studies including both acute and elective cases, BDI rates were 0.5 and 0.25%, respectively [20,21]. Cholecystitis must be considered as a risk factor for BDI, as shown by Gigot et al in a previous national survey of 65 BDI in Belgium [9] in which AC and scleroatrophic gallbladder were present in half of patients. Because of the anonymous inclusion of patients in the present study, the BDI incidence of 1.2% is probably a closer reflection of reality.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The combined hook and thermal dissector related injury was the second common. Thermal injury due to electro cautery occurred in 1/3 of patients (28). A study reviewing the video scopes found that most bile duct injuries involved a combination of mechanisms such as misidentification of the anatomy, transaction, burn or hepatic arterial injury.…”
Section: Mechanisms Of Bile Duct Injurymentioning
confidence: 99%
“…However, due to the limitations in visualization during laparoscopy, common bile duct (CBD) injuries have become significantly more common. The rate of CBD injuries is estimated to be 0.1-0.2% for open cholecycstectomy (OC) and 0.2-1.6% for LC, roughly three times greater than its open counterpart [2][3][4][5][6][7]. These injuries are most often caused by misidentification or misinterpretation of biliary anatomy [8].…”
Section: Introductionmentioning
confidence: 99%